THE EFFECTIVITY OF THE LIBRARY PROMOTION TO THE LIBRARY VISITOR GROWTH IN THE LIBRARY OF HASANUDDIN UNIVERSITY MAKASSAR - Jayanti, Ida; Najib, M; Tike, Arifuddin (Program Pascasarjana, UIN Alauddin Makassar, 2020)
This research is aimed to discover the effectiveness of the library promotion to the growth of the library visitors in the library of Hasanuddin University. This is an associative research with quantitative approach. The population used in this research is the students of Hasanuddin University visiting the central library during 2018 which reached 102.594 visitors in total, while the samples of this research covered only 203 respondents. Research data is collected using both printed and online questionnaire.Hence, the data is processed and analyzed using correlativity test and validity test. According to the testing result, the effectivity of the library promotion variable (X) related to the increase of the library visitors’ growth (Y) in the central library of Hasanuddin University is feeble, with the Pearson correlation value takes only 0,139 or 13,9% and the significancy rate is at 0,000 < 0,05. These numbers indicates the library promotion variable (X) is simultaniously affecting the visitor rate variable (Y) around 19%, while the rest 81% is affected by another variables apart from regression equation and other variables.